MARPLE (Mobile And Real-time PLant disEase) diagnostics. Rapid and accurate point-of-care (PoC) diagnostics for wheat yellow rust - CGIAR Platform for Big Data in Agriculture (2019)
Successful pilot in 2018. Capacity to run the entire MARPLE system was successfully transferred to Ethiopian partners. Accurate diagnosis of yellow rust field samples to genetic group was obtained in Ethiopia within 3 days of sample collection. Methods published in BMC Biology. Winner BBSRC innovator of year - International Impact